2020
DOI: 10.3390/su12083085
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship between Transportation and Communications Industries Complementary or Substitutional? An Asian Countries-Based Empirical Analysis Using Input-Output Accounts

Abstract: The relationship between transportation and communications has been discussed throughout the past decades. This study also investigates that relationship to determine whether they are complementary or substitutive in terms of the industrial perspective, focusing mainly on six Asian countries (China, Japan, India, Korea, Indonesia, and Taiwan). National input-output (I-O) tables from the World Input-Output Database (WIOD) were used to construct research dataset. Each activity in the table was examined and fell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Findings from the study corroborate the studies of Oyesiku (1996) and Choi, Choo, and Kim (2020) that telecommunication cannot fully compensate for face-to-face contact, for instance, the conveyance of complex, non-structured, or potentially ambiguous information. Also, the social and cultural background of people in Nigeria, a developing country, is such that the physical presence of friends and relatives is often appreciated; hence telecommunication may not be able to fully substitute travel.…”
Section: Resultssupporting
confidence: 86%
“…Findings from the study corroborate the studies of Oyesiku (1996) and Choi, Choo, and Kim (2020) that telecommunication cannot fully compensate for face-to-face contact, for instance, the conveyance of complex, non-structured, or potentially ambiguous information. Also, the social and cultural background of people in Nigeria, a developing country, is such that the physical presence of friends and relatives is often appreciated; hence telecommunication may not be able to fully substitute travel.…”
Section: Resultssupporting
confidence: 86%
“…As a basic industry, the PT industry contributes to many other urban industries, such as urban tourism [12]. Choi et al (2020) [13] confirmed the predominant complementary relationship between transportation and communication industries in six Asian countries and regions. Second, PT helps increase territorial cohesion.…”
Section: Public Transportationmentioning
confidence: 82%